The Use of Artificial Intelligence in Scientific Writing at the Faculty of Medicine, Public Health, and Nursing of Gadjah Mada University, Indonesia - Maniso Mustar; Haxa Suprijanto; Amirul Ulum; Agung Nurrahman (Indonesian Journal of Librarianship, 2025)
Problem Statement: Advances in artificial intelligence (AI) technology have had a significant impact in various fields, including academia. FKKMK UGM has recognized the potential of AI to support scientific writing activities within its environment. Purpose: This study aims to describe the use of AI in the scientific writing process at FKKMK UGM. Method: This study employed a survey methodology through the distribution of questionnaires to students. The collected data were analyzed descriptively to assess the levels of knowledge, usage, and perceptions regarding the use of AI in scientific writing. Result: The results of the study indicate that most respondents are aware of AI and its potential in supporting scientific writing. However, the use of AI in scientific writing practices by college students is still limited. Some of the benefits of AI perceived by respondents include grammar checking, plagiarism detection, and reference writing. This study shows that there are four main strategies for utilizing AI in scientific writing at FKKMK UGM, namely: 1) Using AI to assist in the preparation of scientific writing frameworks, 2) Utilizing AI in the editing and grammar correction process, 3) Using AI for data analysis and visualization, and 4) Integrating AI into reference and citation management systems. However, academic community also identified several challenges, such as concerns about plagiarism, high costs, and the need for intensive training for academic community. In practice, respondents also expressed concerns about ethical issues and the quality of AI usage outcomes. Conclusion: This study concludes that there is a great potential for increasing the use of AI in scientific writing at FKKMK UGM. However, efforts are needed to improve understanding and develop guidelines for the use of AI that are in line with the principles of good and proper scientific writing.Keywords: Artificial Intelligence (AI), Scientific Writing, Strategy Implementation, Academic Productivity; Education Technology.